Analysis of discourse and rhetoric in performance measures for research institutions in Kansas - Gott, Trisha (Kansas State University, 2016)
This qualitative discourse analysis examines discourse related to performance-based measures such as, state of the state speeches, policy documents, reports, and other discourse to explore the purpose(s) higher education has in Kansas, as manifested in discourse from 1997 to 2015. The research explores discourse produced by elected and appointed state level officials’ related to higher education policy, purpose, and governance, with a specific focus on performance-based measures in Kansas. The purpose of this research was to understand more fully how discourse shapes and reflects understanding of the role and purpose of higher education in the state of Kansas. This study explored the power of discourse to shape a narrative in a state and influence policy and governance. Using discourse analysis as the methodological framework, this qualitative study included analysis of policy documents, speeches, reports, budgets, and other discourse related to performance-measures in Kansas. Discourse analysis, informed by political and critical discourse analysis were the primary approach to this research. Using a multiperspective approach to data analysis and coding, data was examined for themes of power, social, economic, and political influences. The study has implications for higher education policy and for policymakers, administrators, and other actors in higher education in Kansas.
Keywords: Education policy; Higher education; Administration